Questões da moda, questões das “linguagens” visuais: Intertextualidades possíveis (ModaPalavra e-periódico, 2011)
This paper discusses certain ideas about the relationships that can be established between different “languages” with the intention of amplifying the possibilities for interpretation both of works of art and of everyday esthetics whilst provoking reflection on the creative process. The Los Angeles Museum of Contemporary Art exhibition “Skin and bones: parallel practices in fashion and architecture” (2006-2007) is considered a reference in thinking on the intersemiotic and intertextual relationships between different “languages” within a single system, namely the visual system.
Keywords: fashion; architecture; intertextuality